ʺRelevance of the formation of international strategic educational alliances involving Ukraineʺ - Kharkivska, A.; Kapustina, O. (Problems of Engineer-Pedagogical Education, 2022)
The authors prove that in the process of education internationalization it is important to form general and special competencies, self-organization and self-improvement skills of all representatives of the education sphere and increase the efficiency of interaction between scientists, teachers and students of domestic and foreign higher education institutions. This is possible on the basis of successful cooperation between them. A number of scientific research works of domestic and foreign strategists on the organization of cooperation at the international level were analyzed. The meaning of the concept “strategic alliance” was defined, the content and features of the concept “strategic educational alliance” were analyzed. The feasibility of international strategic educational alliances and the relevance of their formation in Ukraine were determined. The process of internationalization of education is proved to include such forms of international cooperation as mobility of graduates and teaching staff; integration of educational programs; institutional partnerships that contribute to the creation of strategic educational alliances. Interaction and cooperation within the framework of strategic educational alliances is the most flexible form of integration of education institutions into the transnational education space, which at the same time retains the right to be independent. The development of international educational alliances with the participation of domestic universities is confirmed to be essential, as it is aimed at strengthening the innovative potential of the European and national education spaces, encouraging innovation in higher education, business and the broader socio-economic area, contributing to the goals and mutually beneficial results, and increasing the chance that the Ukrainian education system will enter the global education market.